Analytical prediction of groundwater loss in deep coal mines induced by ground vibration - Pieride Mabe Fogang; Bingjie Huo; Hervé Losaladjome Mboyo; Rong Hai; Songtao Zhang; Lesly Dasilva Wandji Djouonkep; Dieudonné Bisso (Scientific Reports)
Abstract Deep coal mining induces geomechanical perturbations that threaten aquifer integrity. This study develops an analytical model coupling Fourier’s heat conduction and Cauchy’s momentum equations to predict groundwater depletion under dynamic stress from vibrations (0–6 MPa). Laboratory tests on Datong Mine samples (coal seam No. 12) yielded baseline parameters, including soil cohesion (C = 1.0 MPa) and Poisson ratio (ν = 0.35). The simulation uses an effective elastic modulus (E = 12.5 GPa) to represent the fractured coal-rock mass under vibrational loading. Results show vibration-induced fractures increase permeability by 15–25% initially, but subsequent compaction reduces it by 60%, with peak vertical displacements of 0.18 m. Vibrational loads exceeding a critical stress magnitude of 6 MPa exacerbate hydraulic conductivity variations, altering pore pressure distributions and threatening aquifer integrity. The model, validated via ABAQUS simulations, provides a scalable tool for mitigating water loss in mining environments. This research highlights the criticality of harmonizing geomechanical simulations with hydrogeological assessments to advance groundwater management strategies. The proposed analytical solution offers a scalable solution for mitigating environmental and operational risks across diverse mining geologies, ensuring resource sustainability and operational resilience against geohydrological instabilities.